Spinal changes of a newly isolated neuropeptide endomorphin-2 concomitant with vincristine-induced allodynia. - Yang Yang; Yong-Gang Zhang; Guo-An Lin; He-Qiu Xie; Hai-Tao Pan; Ben-Qing Huang; Ji-Dong Liu; Hui Liu; Nan Zhang; Li Li; Jian-Hua Chen (PLoS ONE)
Chemotherapy-induced neuropathic pain (CNP) is the major dose-limiting factor in cancer chemotherapy. However, the neural mechanisms underlying CNP remain unclear. There is increasing evidence implicating the involvement of spinal endomorphin-2 (EM2) in neuropathic pain. In this study, we used a vincristine-evoked rat CNP model displaying mechanical allodynia and central sensitization, and observed a significant decrease in the expression of spinal EM2 in CNP. Also, while intrathecal administration of exogenous EM2 attenuated allodynia and central sensitization, the mu-opioid receptor antagonist β-funaltrexamine facilitated these events. We found that the reduction in spinal EM2 was mediated by increased activity of dipeptidylpeptidase IV, possibly as a consequence of chemotherapy-induced oxidative stress. Taken together, our findings suggest that a decrease in spinal EM2 expression causes the loss of endogenous analgesia and leads to enhanced pain sensation in CNP.